PENGARUH MODEL NHT (NUMBER HEAD TOGETHER) TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS DI SD NEGERI 054/VIII SUNGAI KERUH - Sahrul pahmi; Eddy Haryanto; Bunga Ayu Wulandari (Postgraduate, University of Mataram, 2025)
The cooperative learning model of the Numbered Heads Together (NHT) type is essentially a variation of group discussion, characterized by the teacher selecting only one student to represent their group. The problem in this study is the lack of implementation of learning models in teaching and learning activities. The purpose of this research is to determine the influence of the NHT (Numbered Heads Together) model on learning outcomes in the IPAS subject. This study is experimental research with a one-group pretest-posttest design. The population of this research includes all first to sixth-grade students at SDN 054/VIII Sungai Keruh in the 2023/2024 academic year, totaling 211 students. The research sample consists of 29 students. The data collection technique used was a test technique. Based on the results of the paired samples t-test, the significance value obtained was 0.000 < 0.05, which means that H₀ is rejected and Hₐ is accepted. It is concluded that the NHT (Numbered Heads Together) model has an impact on the IPAS subject in terms of the learning outcomes of fourth-grade students at SDN 054/VIII Sungai Keruh. Based on this study, the NHT (Numbered Heads Together) model can have a very positive influence on students' learning outcomes in IPAS.